Diversity of NC10 bacteria associated with sediments of submerged Potamogeton crispus (Alismatales: Potmogetonaceae) - Wang, Binghan (PeerJ, 2018)
BACKGROUND: The nitrite-dependent anaerobic methane oxidation (N-DAMO) pathway, which plays an important role in carbon and nitrogen cycling in aquatic ecosystems, is mediated by “Candidatus Methylomirabilis oxyfera” (M. oxyfera) of the NC10 phylum. M. oxyfera-like bacteria are widespread in nature, however, the presence, spatial heterogeneity and genetic diversity of M. oxyfera in the rhizosphere of aquatic plants has not been widely reported. METHOD: In order to simulate the rhizosphere microenvironment of submerged plants, Potamogeton crispus was cultivated using the rhizobox approach. Sediments from three compartments of the rhizobox: root (R), near-rhizosphere (including five sub-compartments of one mm width, N1–N5) and non-rhizosphere (>5 mm, Non), were sampled. The 16S rRNA gene library was used to investigate the diversity of M. oxyfera-like bacteria in these sediments. RESULTS: Methylomirabilis oxyfera-like bacteria were found in all three sections, with all 16S rRNA gene sequences belonging to 16 operational taxonomic units (OTUs). A maximum of six OTUs was found in the N1 sub-compartment of the near-rhizosphere compartment and a minimum of four in the root compartment (R) and N5 near-rhizosphere sub-compartment. Indices of bacterial community diversity (Shannon) and richness (Chao1) were 0.73–1.16 and 4–9, respectively. Phylogenetic analysis showed that OTU1-11 were classified into group b, while OTU12 was in a new cluster of NC10. DISCUSSION: Our results confirmed the existence of M. oxyfera-like bacteria in the rhizosphere microenvironment of the submerged plant P. crispus. Group b of M. oxyfera-like bacteria was the dominant group in this study as opposed to previous findings that both group a and b coexist in most other environments. Our results indicate that understanding the ecophysiology of M. oxyfera-like bacteria group b may help to explain their existence in the rhizosphere sediment of aquatic plant.